ANALISIS POTENSI SUMBER DAYA ALAM DALAM MENGEMBANGKAN SEKTOR PARIWISATA DI KABUPATEN SAMOSIR - Hasibuan, Silvia Annur; Manik, Monika Flora; Sitohang, Mizael Demak; Sianturi, Rejosu Vanhot; Purba, Bonaraja (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
Samosir Regency is a regency that has very diverse natural resources, making it a popular tourist destination in Indonesia. This regency has the potential for natural resources that are very worthy of being developed in order to attract the attention of local and international tourists. The objectives of this study are: (1) to identify the potential of natural resources for tourism development in Samosir Regency, (2) to analyze the strategic development of tourism potential in Samosir Regency. The method used is a qualitative method with a literature approach and data obtained through BPS and various literature studies such as books, journals and articles. The results of this study indicate that the potential for natural resources in Samosir Regency to be used as tourism objects is very diverse, such as beaches, waterfalls, historical sites, natural baths, nature tourism and caves and others have the potential to increase economic growth for the community. However, the government, community, and business actors need to implement several strategies for tourism destinations in Samosir Regency, such as the construction of public facilities such as toilets, unique photo spots, improving road conditions in certain locations and clear, informative and easy-to-understand signposts.